Vertical Writing Connected (The Utility of Vertical Connected in Elementary School) - Jihan Inas Zharifah; Prahasiwi Cahya Pangesti; Rahma Putri Andriani (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
In Indonesia, the writing has developed. In the past, the writing was in italic andcontinuous form, but in 1983 the government issued a regulation regarding the standardform of writing. Writing in cursive with its unique form has many benefits, Cursivewriting is an activity to form continuous writing. Writing cursive is the process offorming letters that are related to each other to form a word, on a flat plane using awriting utensil. Curved letters are one of the unique types of writing. In the internationalworld, cursive writing is known as cursive writing.